Finance, economic planning and power in Zimbabwe, 1980-2013 - Sibanda, Geraldine Jacquline (University of the Free State, 2021)
This thesis is an examination of economic planning, state finance and power in Zimbabwe up to 2013. It contributes to debates that unpack the nature of the postcolonial regime and how the economy was structured to ensure its survival. The thesis adds to this debate by arguing that an elite group manipulated economic planning and financial processes thereby keeping the regime in power during the period under review. The study utilises a wide selection of sources including reports from governmental and non-governmental bodies, parliamentary debates, correspondence, and interviews with former ministers and governors, to argue that this elite comprised cabinet, high-ranking civil servants, and IFIs. The elite made major economic policy and state finance decisions at the expense of the public and Parliament. Arranged chronologically, the thesis demonstrates the interlinkages of this class in different epochs. Similarly, the thesis demonstrates the importance of inherited economic management systems in shaping economic planning and state finance during the period under review as weaknesses in the systems provided ample room for the elite to manipulate these systems and ensure power retention. The study makes a sustained analysis of government’s expenditure patterns revealing the regime’s unsustainable spending patterns that created fiscal crises. Likewise, government revenue allocation patterns show cabinet’s manipulation of inherited systems to finance the security sector at the expense of expenditure towards economic, infrastructure and social development. Due to unending fiscal crises, to finance its expenditure and ensure power retention, cabinet turned to fiddling with monetary policy since 2000 which included offloading bank reserves, money expansion, issuance of too many treasury bills, and what this thesis terms currency engineering, that is, the introduction of pseudo-currencies and currency rebasing. Finally, the thesis shows the role of IFIs in financing the postcolonial state which was heavily dependent on foreign borrowing since 1980. Together with IFIs, cabinet acquired debt not in the best interests of the population thereby making a compelling case for postcolonial odious debt. It concludes that both the inherited economic management systems and the power retention agenda accounted for Zimbabwe’s economic and political predicament during the period under review.
Thesis (Ph.D. (Centre for Africa Studies))--University of the Free State, 2021
Keywords: Economic planning; State finance; Inherited economic management systems; Odious debt; Power retention; Currency engineering